Efficacy and safety of once-daily nitisinone for patients with alkaptonuria (SONIA 2): an international, multicentre, open-label, randomised controlled trial. Issue 9 (September 2020) - Ranganath, Lakshminarayan R; Psarelli, Eftychia Eirini; Arnoux, Jean-Baptiste; Braconi, Daniela; Briggs, Michael; Bröijersén, Anders; Loftus, Nadia; Bygott, Helen; Cox, Trevor F; Davison, Andrew S; Dillon, Jane P; Fisher, Michael; et al.
Summary: Background: Alkaptonuria is a rare, genetic, multisystem disease characterised by the accumulation of homogentisic acid (HGA). No HGA-lowering therapy has been approved to date. The aim of SONIA 2 was to investigate the efficacy and safety of once-daily nitisinone for reducing HGA excretion in patients with alkaptonuria and to evaluate whether nitisinone has a clinical benefit. Methods: SONIA 2 was a 4-year, open-label, evaluator-blind, randomised, no treatment controlled, parallel-group study done at three sites in the UK, France, and Slovakia. Patients aged 25 years or older with confirmed alkaptonuria and any clinical disease manifestations were randomly assigned (1:1) to receive either oral nitisinone 10 mg daily or no treatment. Patients could not be masked to treatment due to colour changes in the urine, but the study was evaluator-blinded as far as possible. The primary endpoint was daily urinary HGA excretion (u-HGA24 ) after 12 months. Clinical evaluation Alkaptonuria Severity Score Index (cAKUSSI) score was assessed at 12, 24, 36, and 48 months. Efficacy variables were analysed in all randomly assigned patients with a valid u-HGA24 measurement at baseline. Safety variables were analysed in all randomly assigned patients. The study was registered at ClinicalTrials.gov (NCT01916382 ). Findings: Between May 7, 2014, and Feb 16, 2015, 139 patients were screened, of whom 138 were included in the study, with 69 patients randomly assigned to each group. 55 patients in the nitisinone group and 53 in the control group completed the study. u-HGA24 at 12 months was significantly decreased by 99·7% in the nitisinone group compared with the control group (adjusted geometric mean ratio of nitisinone/control 0·003 [95% CI 0·003 to 0·004], p<0·0001). At 48 months, the increase in cAKUSSI score from baseline was significantly lower in the nitisinone group compared with the control group (adjusted mean difference –8·6 points [–16·0 to –1·2], p=0·023). 400 adverse events occurred in 59 (86%) patients in the nitisinone group and 284 events occurred in 57 (83%) patients in the control group. No treatment-related deaths occurred. Interpretation: Nitisinone 10 mg daily was well tolerated and effective in reducing urinary excretion of HGA. Nitisinone decreased ochronosis and improved clinical signs, indicating a slower disease progression. Funding: European Commission Seventh Framework Programme.